2019
DOI: 10.1080/19490976.2019.1667722
|View full text |Cite
|
Sign up to set email alerts
|

Origins of human milk microbiota: new evidence and arising questions

Abstract: Human milk contains a diverse community of bacteria. The growing appreciation of commensal microbes and increasing availability of high-throughput technology has set the stage for a theory-driven approach to the study of milk microbiota, and translation of this knowledge to improve maternal and child health. We recently profiled the milk microbiota of healthy Canadian mothers and applied theory-driven causal modeling, finding that mode of breast milk feeding (nursing directly at the breast vs. pumping and feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 57 publications
4
75
0
6
Order By: Relevance
“…Clinical studies demonstrating ingested probiotic strains were identified in maternal breast milk further support this hypothesis 85,86 . More information about the origin of milk microbes can be found in this review by Moossavi et al 87 …”
Section: Early Colonization In Healthy Newbornsmentioning
confidence: 81%
“…Clinical studies demonstrating ingested probiotic strains were identified in maternal breast milk further support this hypothesis 85,86 . More information about the origin of milk microbes can be found in this review by Moossavi et al 87 …”
Section: Early Colonization In Healthy Newbornsmentioning
confidence: 81%
“…Species belonging to the Methylobacterium genus are prevalent in water pipes and reservoirs (Barbeau et al, 1996;Vaz-Moreira et al, 2017) and as contaminants of industrial milk samples (Bracke et al, 2014). In addition, some studies also indicate that Methylobacterium species are part of the human oral and skin microbiota (Hung et al, 2011;Alekseyenko et al, 2013) and, therefore, their presence in breast milk microbiota could partly be due to their transmission via the infant's oral cavity, an event that has been recently hypothesized as important modulator of the hMM (Moossavi and Azad, 2019;. Interestingly, a recent microbiota analysis of human breast tissue through 16S rRNA gene amplicon sequencing has also reported the presence of Methylobacterium (among other environmental microbes such as Ralstonia) in healthy and cancerous breast biopsies (Costantini et al, 2018), supporting the presence of these type of microbes in human breast-related samples.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of the current study included the fact that the human milk fed to piglets represented a pool of donor milk. The interindividual variations of milk composition between donor mothers, including fatty acids ( 71 ), metabolites ( 72 ), oligosaccharides ( 73 ), and microbiota ( 74 ), might alter intestinal metagenome and transcriptome. However, the pooled HM used in the current study likely eliminated the impact of interindividual variations of HM on intestinal functions in piglets.…”
Section: Discussionmentioning
confidence: 99%